Perforation of Meckel's diverticulum caused by a chicken bone: a case report - Chan, Kim W (BioMed Central, 2009)
INTRODUCTION: Meckel's diverticulum represents a true diverticulum of the ileum containing all three layers of the bowel wall and is found on the wall of the distal ileum, usually about 2 feet from the ileocaecal valve. Although Meckel's diverticulum is a common congenital abnormality of the gastrointestinal tract, it is often difficult to diagnose. Patients with perforation of Meckel's diverticulum may present with right iliac fossa pain, which mimics acute appendicitis. CASE PRESENTATION: A 17-year-old man presented with a 3-day history of lower abdominal pain. On examination, the patient had tenderness in his right iliac fossa. A provisional diagnosis of acute appendicitis was made. The patient was taken to theatre for laparoscopy with the option of appendicectomy. The appendix was found to be normal. An inflamed and perforated Meckel's diverticulum was found to be the cause of the abdominal pain. Meckel's diverticulectomy was performed. The patient made an uneventful recovery and was discharged with further follow-up in the outpatient clinic. CONCLUSION: Complications of Meckel's diverticulum can be fatal and early recognition leads to appropriate management. This case report highlights the importance of considering Meckel's diverticulum as a differential diagnosis of acute abdomen in a young patient.